Hospital Based Study of Poisoning Among Children, 1 to 18 Years of Age in Eastern Nepal - Rwimal, Hem Sagar; Tiwari, U; Ghimire, K; Thapa, M (Birat Journal of Health Sciences, 2017)
Introduction The poisoning among children had been a major cause of hospital admission and also a significant global health problem throughout the world including Nepal. There are various studies suggestive of incidence rate of poisoning in children ranging from 0.74% to 3%. In older children, poisoning is usually intentional where as in infants and younger children it is accidental in nature There are few studies done in Nepal and they are mainly from Kathmandu valley, this study will add more information from eastern region of Nepal. Objective This study aimed to find out the type of poisoning among children and adolescents, manner of poisoning and its outcomes. Methodology This was a retrospective study carried out at Nobel Medical College Teaching Hospital over a period of one year starting from 1st August 2014 to 31 July 2015. This study included all the children and adolescents of 1 to 18 years of age admitted to pediatric ward and ICU for the management of poisoning. The information including name of poisons, manner of poisoning, socio-economic and demographic factors related to poisoning, geographical distribution of sample population, durations of hospital stay and outcome of treatment were retrieved from the records. The data was analyzed using SPSS. Susceptibility, urinary tract infection, uropathogens. Results A total of 64 cases were studied. It included almost the same number of males (n=31) and females (n=33). The age group of 13-18 years had the largest prevalence of poisoning (n=22). Organo-phosphorus (n=25) was the commonest poison. As the study was conducted in a tertiary care center of eastern Nepal located at Biratnagar, Morang district, a majority of the cases (39) were from Morang. A total of 41% children required hospital stay for more than 7 days where as 37% of them required 5-7 days of hospital stay and only 22% children stayed for 1-4 days in the hospital. No mortality was noted. Conclusion The pediatric poisoning in eastern Nepal is a significant public health issue and nature of poisoning was accidental followed by suicidal. The commonest age group involved is adolescence, which highlights the need for education and implementation of suicidal prevention programming this region. The higher prevalence of accidental poisoning in first two year of life necessitates the need of child safety and injury prevention program in the community. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 138-141